Obesity increases the prevalence and severity of focal knee abnormalities diagnosed using 3T MRI in middle-aged subjects—data from the Osteoarthritis Initiative - Laberge, Marc A.; Baum, Thomas; Virayavanich, Warapat; Nardo, Lorenzo; Nevitt, M. C.; Lynch, J.; McCulloch, C. E.; Link, Thomas M (Skeletal radiology, 2012)
Objective To study the effect of BMI on the prevalence, severity, and 36-month progression of early degenerative changes in the knee by using 3T MRI in middle-aged subjects without radiographic osteoarthritis (OA). Materials and methods We examined baseline and 36-month follow-up MR studies from 137 middle-aged individuals (45-55 years old) with risk factors for knee OA but no radiographic OA from the Osteoarthritis Initiative. Subjects were grouped into three categories: normal BMI (BMI < 25 kg/m 2 , n = 38), overweight (BMI 25–29.9 kg/m 2 , n = 37), and obese (BMI ≥ 30 kg/m 2 , n = 62). Using 3T MRI, cartilage, meniscus, and bone marrow abnormalities were graded using the OA Whole-organ MR Imaging Score (WORMS). The statistical analysis was corrected as necessary for differences in age, sex, and OA risk factors other than BMI. Results The overall prevalence of lesions was 64% for meniscus and 79% for cartilage (including low grade lesions). At baseline, the prevalence and severity of knee lesions was positively associated with BMI, with a nearly fourfold increase in meniscal tears and more than twofold increase in high-grade cartilage defects in obese individuals relative to normal-weight subjects. Over the 36-month follow-up period, the number of new or worsening cartilage lesions of any grade was significantly higher in obese subjects ( p = 0.039), while there was no significant difference in meniscal lesion progression. Conclusion Obesity was associated with both higher prevalence and severity of early degenerative changes in the knee in middle-aged individuals without radiographic OA and with significantly increased cartilage lesion progression (of any grade) over 36 months.